Efficacy of a topical formulation of Henna (Lawsonia inermis) on the itch and wound healing in patients with epidermolysis bullosa: A pilot single-arm clinical trial - Niazi, Mehdi; Parvizi, Mohammad Mahdi; Saki, Nasrin; Parvizi, Zahra; Mehrbani, Mehrzad; Heydari, Mojtaba (Dermatology Practical & Conceptual, 2022)
Introduction: Epidermolysis bullosa (EB) is a rare inherited genetic skin disorder with severe skin itching and recurrent blisters and erosion. There is no effective and specific therapy for all types of EB.Objective: The aim of this study was to evaluate a topical formulation of henna (Lawsonia inermis L.) in the management of wounds and the itching sensation in patients with EB.Methods: This is a pilot single-arm clinical trial. Nine patients with recessive dystrophic EB (RDEB), with the age range of 5 to 32 years old were enrolled in the study. The patients were instructed to apply the topical 1% henna ointment once daily on two erosions and on also two sites with moderate to a severe itching sensation. The total duration of the intervention was four weeks with weekly follow-up visits. Patient global impression of improvement (PGI-I), visual analog scale (VAS), and clinical global impression of improvement (CGI-I) were used for assessing the wound healing process and itching discomfort.Results: There was a significant improvement in the skin symptoms of epidermolysis bullosa including skin redness, itching, burning, and local warmness (p-value<0.05). Local pain decreased during the study period, but this was not statistically significant (p-value<0. 0.19). One patient reported moderate xerosis of skin after continuous usage.Conclusion: It seems that the topical formulation of henna may be effective in the management of itching, burning, stringing, and cutaneous warmness sensation in patients with EB. Further controlled studies with larger sample sizes are recommended to better evaluate this formulation.